Studi Morfometrik dan Meristik Ikan Lemeduk (Barbodes schwanenfeldii) di Sungai Belumai Kabupaten Deli Serdang Morphometric and Meristic Study of Lemeduk Fish (Barbodes schwanenfeldii) in Belumai River Deli Serdang Regency - Anita Rahman; Miswar Budi Mulya; Desrita Desrita (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2015)
Belumai river is one of river in Deli Serdang Regency, North Sumatra Province. One of fish resource potency in Belumai river is Lemeduk fish (Barbodes schwanenfeldii). The aims these research are to study the morphometric characteristic and meristic range and to observe the morphometric diversity Lemeduk fish in Belumai river. This study was conducted in Belumai River Deli Serdang Regency from May until June 2014. The calculation morphometric character using Principal Component Analysis based on morphometric character. The results of Principal Component Analysis indicate more information were found on the both of principal component with cumulative range was 84,3%. All morphometric character had a role on first main component. The character with a role to the second main component as character that influence the morphometric diversity was dorsal fin length and eye diameter. The principal component analysis indicated lemeduk fish on four stations did not indicate classification. This indicate that the observed fish was one population unit. On the calculation phenotype range value each character lemeduk fish in Belumai river indicate that morphometric character with the higher range value was standart length (PS) and the lower is eye diameter (DM), and meristic character calculation found the radius fin were DIII.9, AIII.6, VI.8, P.13 −14.Keywords :Morphometric, Meristic, Belumai River, Barbodes schwanenfeldii